Dimension of Big Five Personality and Resilience in Adolescents who are Pregnant Out of Wedlock - Djasmita, Ketrin Putri; Huwae, Arthur (Psychocentrum Review, 2023)
Adolescents pregnancies out of wedlock have many negative impacts on adolescents. Among them are prolonged trauma, a crisis of self-confidence, getting various psychological shocks and the most influential on the personality of the adolescents themselves. Personality in adolescents who are pregnant out of wedlock can help adolescents to maintain resilience in dealing with various kinds of negative impacts due to pregnancy out of wedlock. Therefore, this research aims to investigate the relationship between the dimensions of the big five personality and resilience in adolescents who are pregnant out of wedlock. The method used was quantitative with a correlational design. A total of 102 adolescents who are pregnant out of wedlock became participants in this research with the sampling technique used was incidental sampling. This study used the Big Five Inventory scale with each dimension extraversion (α = 0.762), agreeableness (α = 0.751), conscientiousness (α = 0.797), openness to experience (α = 0.758) and neuroticism (α = 0.690) and Connor-Davidson Resilience Scale (α= 0.864). The data analysis method in this research used the product moment correlation test from Karl Pearson. The results of the research proved that there was no relationship between extraversion and resilience (r=0.023 with sig.=0.410 (p>0.05)), there was no relationship between agreeableness and resilience (r=0.016 with sig.=0.437 (p>0, 05)), conscientiousness with resilience (r=0.107 with sig.=0.143 (p>0.05)), openness to experience with resilience (r=0.072 with sig.=0.236 (p>0.05)), neuroticism with resilience (r=-0.099 with sig.=0.162 (p>0.05)). This showed that personality, in this case the big five personality was not one of the factors associated with increasing or decreasing resilience in adolescents who are pregnant out of wedlock.